Proceedings of the 14th International Symposium on Nuclei in the Cosmos (NIC2016) 2017
DOI: 10.7566/jpscp.14.010901
|View full text |Cite
|
Sign up to set email alerts
|

The s-Process Nucleosynthesis in Extremely Metal-Poor Stars as the Generating Mechanism of Carbon Enhanced Metal-Poor Stars

Abstract: The origin of carbon-enhanced metal-poor (CEMP) stars plays a key role in characterising the formation and evolution of the first stars and the Galaxy since the extremely-metal-poor (EMP) stars with [Fe/H] ≤ −2.5 share the common features of carbon enhancement in their surface chemical compositions. The origin of these stars is not yet established due to the controversy of the origin of CEMP stars without the enhancement of s-process element abundances, i.e., so called CEMP-no stars. In this paper, we elaborat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…CEMP-no stars are traditionally assumed to have formed from a previous generation of massive stars from which they inherited their chemical peculiarities, but doubts have been cast on this hypothesis. Considering the continuity of the [Ba/C] distribution as a function of [Fe/H] in CEMP-s and CEMPno stars, Abate et al (2015b) and Suda et al (2017a) suggested that CEMP-s and (some) CEMP-no objects might have a common origin involving binarity. Observational studies that analysed the binary fraction of different subclasses of CEMP stars support this hypothesis (Starkenburg et al, 2014;Hansen et al, 2016a).…”
Section: Present Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…CEMP-no stars are traditionally assumed to have formed from a previous generation of massive stars from which they inherited their chemical peculiarities, but doubts have been cast on this hypothesis. Considering the continuity of the [Ba/C] distribution as a function of [Fe/H] in CEMP-s and CEMPno stars, Abate et al (2015b) and Suda et al (2017a) suggested that CEMP-s and (some) CEMP-no objects might have a common origin involving binarity. Observational studies that analysed the binary fraction of different subclasses of CEMP stars support this hypothesis (Starkenburg et al, 2014;Hansen et al, 2016a).…”
Section: Present Open Questionsmentioning
confidence: 99%
“…The heavier species synthesised would then act as seeds to form s-process elements. Once transported to the surface by third dredge-up, these stars are expected to display Pb and Bi enhancements [see also Suda, Yamada, & Fujimoto (2017a)]. Cruz et al (2013) also computed and analysed s-process nucleosynthesis in 1 M stars between primordial and Z = 10 −7 .…”
Section: Nucleosynthesis In Emp Stars Undergoing 'Normal' Thermally Pmentioning
confidence: 99%